Respostas
respondido por:
0
2 - 2 = x
---------- ----------
x² - 1 x - 1
2 - 2.(x + 1).(x - 1) = x.(x + 1)
--------------------------------------- ------------------
(x + 1).(x - 1) (x + 1).(x - 1)
2 - 2.(x² - 1) = x² + 1
2 - 2x² + 2 = x² + 1
4 - 2x² = x² + 1
4 - 1 = x² + 2x²
3 = 3x²
3x² = 3
x² = 3/3
x² = 1
x = √1
x = +/- 1
R.: { - 1,1}
---------- ----------
x² - 1 x - 1
2 - 2.(x + 1).(x - 1) = x.(x + 1)
--------------------------------------- ------------------
(x + 1).(x - 1) (x + 1).(x - 1)
2 - 2.(x² - 1) = x² + 1
2 - 2x² + 2 = x² + 1
4 - 2x² = x² + 1
4 - 1 = x² + 2x²
3 = 3x²
3x² = 3
x² = 3/3
x² = 1
x = √1
x = +/- 1
R.: { - 1,1}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás